Transcription factors Sox10 and Sox2 functionally interact with positive transcription elongation factor b in Schwann cells - Arter, Juliane; Wegner, Michael (Journal of Neurochemistry, 2015)
Sox proteins are mechanistically versatile regulators with established relevance to different developmental processes and crucial impact on chromatin structure, DNA conformation, and transcriptional initiation. Here, we show that Sox2 and Sox10, two Sox proteins important for Schwann cell development, also have the capability to activate transcriptional elongation in a Schwann cell line by recruiting the positive transcription elongation factor b. Recruitment is mediated by physical interaction between the carboxyterminal transactivation domains of the two Sox proteins and the Cyclin T1 subunit of positive transcription elongation factor b, with interaction interfaces for the two Sox proteins being mapped to adjacent regions of the central part of Cyclin T1. Supporting the relevance of this interaction to Schwann cell development, transcription of myelin genes appears regulated at the level of elongation. Our results thus add a new facet to the activity of Sox proteins and expand the functional repertoire of this important group of developmental regulators. Sox transcription factors are important regulators of nervous system development. While they are known to regulate transcription by recruiting and stabilizing the RNA polymerase II preinitiation complex directly or with help of the Mediator complex, this study provides evidence that Sox10 and Sox2 additionally influence transcription in glial cells at the elongation stage by recruiting P-TEFb. Cdk9, cyclin-dependent kinase 9; P-TEFb, positive transcription elongation factor b; Pol II, RNA polymerase II; Sox, Sox2 or Sox10 protein.
EVALuna2:4977